Study on heating performance of solar-assisted heat pump drying system under large temperature difference. (15th November 2021) - Li, Jin; Zhang, Ying; Li, Ming; Wang, Yunfeng; Shi, Mingyuan; Gao, Meng; Deng, Zhihan; Lu, Gansong; Liu, Rui
Highlights: The performance fluctuation of HPD system was given quantitatively. A new SHPD system for large temperature difference conditions was proposed. COP of SHPD mode is 1.8 times higher than that of HPD mode under the same conditions. Abstract: In this study, a heat pump drying (HPD) system platform complemented by solar hot water was designed and established. The objective was to address the declines in the heating performance of air source HPD at high altitudes (more than 3000 m), cold conditions (annual average temperature at 5 °C), and with large temperature differences between day and night (more than 20 °C), i.e. under harsh conditions. A theoretical model was derived to determine the system parameters and to support the experimental analysis. Under no-load conditions, four cases with ambient temperature were tested and compared to explore the relationships between the system parameters and performance, as well as the effectiveness of the supplementary solar hot water. The heating performances under HPD and solar-assisted HPD (SHPD) modes were compared and analysed under load conditions (930 kg Mu Xiang). The results indicate that a decrease in the ambient temperature and increase in the temperature in the drying room causes attenuations of the compressor mass flow rate, evaporator cooling power, condenser heating power, and system coefficient of performance ( COP ). In addition, solar water heating can significantly improve the heating performance of the HPD system. Under no-load conditions, the average heating power of the HPD-mode system is 19.27 kW, and the average COP is 2.76. The average heating power of the SHPD mode system is 23.34 kW, and the average COP of the system reaches 3.24, an increase of 17.4%. Under load conditions, the average heating capacity power of the HPD mode is 9.64 kW; the COP is only 1.34, and fluctuates significantly with the decrease in ambient temperature. The average heating capacity power of the SHPD mode is 17.62 kW and the COP is 2.42, i.e. 1.8 times of that of the HPD mode. By raising the drying room temperature to the same set temperature, the SHPD mode time is shortened by 70%.